al-Malamih al-da'wiyah fi qissah Musa ma'a fir'aun fi al-Qur'an al-karim = Da'wah approach in the story of Moses with pharaoah in the Holy Quran : an analytical study / Taher Ahmed Mohammed al-Reyami - al-Reyami, Taher Ahmed Mohammed (2011)
The research started with a introductory chapter about story’s personas that the research was centered around, and short note about Musa, may peace be on him, and Pharaoh. Then, it talked about the events of the story through the verses of the Holy Qur’an according to the order in it, and according to the needed elaboration and concision with mentioning what the most well-known Qur’an interpreters (Mufasiroon), and some short commentaries serving the topic of concern. Next, it is necessary to explore the most important issues Musa, may peace be on him, had focused on while making dawah where he used to talk about tawheed (oneness) of Allah, and warn from shirk (polytheism). After that, the research talked about the essence of the whole thesis, its most important part, which is Dawah means and forms Musa used while inviting Pharaoh. Then I mentioned the most significant aspects and forms of Dawah the callers to Allah can benefit from through Musa’s story. Eventually, the research laid down the factors of success in the Dawah of Musa, may peace be on him, and how callers to Allah can utilize those factors, as a part of taking tangible causes today so that they can realize success. The research included a lot of lessons, and in the conclusion, the research focused on the most important of those lessons, and the results of this research. I ask Allah to bestow on us His guidance.